Ralstonia picketti neonatal sepsis: a case report. (December 2017) - Sharma, Deepak; Sharma, Pradeep; Soni, Priyanka; Gupta, Basudev
Abstract Background Ralstonia genus are gram negative bacillus and includes four bacteria namelyRalstonia picketti, Ralstonia Solanacearum, Ralstonia insidiosa andRalstonia mannitolilytica . These are opportunistic pathogens and cause infections in immunocompromised host. The sources of infection are usually contaminated solutions and water. The majority of the reported cases are caused byR. picketti . It is very rare cause of neonatal sepsis with less than twenty cases reported in literature till date. Case presentation A late preterm male infant, Indian race was admitted to the neonatal intensive care unit for respiratory distress developing soon after birth. The infant was managed with respiratory support and gradually infant improved and diagnosis of transient tachypnea of newborn was made. At age of 84 h of postnatal life, the infant developed features of neonatal sepsis and investigations were suggestive of sepsis. The infant was started on intravenous antibiotic, multiple vasopressors and steroids. The blood culture showed growth of multi-drug resistantR. picketti . The antibiotics were changed as per sensitivity pattern and infant was discharged in good condition and was accepting breast feeding at the time of discharge. There was also no other case ofR. picketti in the nursery during the same time period. Conclusion Ralstonia picketti is an uncommon cause of neonatal sepsis and usually source of infection are contaminated solutions and medical products. The management involves early detection, treatment with appropriate antibiotics and doing surveillance culture to identify the possible source of infection.